Strength-power performance of visually impaired Paralympic and Olympic judo athletes from the Brazilian national team: A comparative study - Loturco, I.; Nakamura, F. Y.; Winckler, C.; Bragança, J. R.; da Fonseca, R. A.; Filho, J. M.; Zaccani, W. A.; Kobal, R.; Cal Abad, C. C.; Kitamura, K.; Pereira, L. A.; Franchini, E. (The Journal of Strength and Conditioning Research, 2017)
The aim of this study was to compare the muscle power and maximal isometric strength capacities of Olympic and visually impaired Paralympic judo athletes. Twenty-eight elite judo athletes (7 men and 7 women per group) from the permanent Brazilian National Paralympic and Olympic teams took part in this study. After a specific warm-up, the athletes performed loaded jump squat (JS), bench press (BP), and standing barbell row (SBR) exercises to determine their values of maximum mean propulsive power (MPP) in these respective exercises. The maximal isometric strength (MIS) was also determined for both upper and lower limbs, through the use of BP and half-squat (HS) exercises. Finally, the jumping ability was assessed using unloaded squat jump (SJ). The magnitude-based inference was used to compare the groups. The Olympic judo athletes presented a likely higher SJ height than the Paralympic athletes. The Olympic group presented almost certainly higher MPP in the loaded JS and in the SBR exercises and likely higher MPP in the BP exercise. Importantly, in the MIS assessments the differences between groups in the HS and BP exercises were rated as unclear. In conclusion, our results showed that both Olympic and Paralympic judo athletes present similar levels of maximal isometric strength, but muscle power performance is superior in Olympic athletes.